2023
DOI: 10.7759/cureus.35760
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Enhanced Recovery After Surgery Protocols in Patients With Perforated Duodenal Ulcer

Abstract: BackgroundEnhanced recovery after surgery (ERAS) protocols are nowadays considered the standard of care for various elective surgical procedures. However, its utilization remains low in tier-two and tier-three cities of India, and there exists a significant variation in the practice. In the present study, we have investigated the safety and feasibility of these protocols or pathways in emergency surgery for perforated duodenal ulcer disease. MethodsA total of 41 patients with perforated duodenal ulcers were ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Finally, six studies with a total cohort of 356 patients were included. [12][13][14][15][16][17] No patients were lost to follow-up. List of included studies and evidence grading as well as risk of bias are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, six studies with a total cohort of 356 patients were included. [12][13][14][15][16][17] No patients were lost to follow-up. List of included studies and evidence grading as well as risk of bias are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, six studies with a total cohort of 356 patients were included 12–17 . No patients were lost to follow‐up.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, available studies about enhanced perioperative care in emergency general surgery are few, sparse and very heterogeneous. In addition, the perioperative care protocol derived from the elective ERAS protocol but with several and substantial differences [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Tables 1 and 2 show in detail the protocols adopted in the evaluated studies.…”
Section: Evidence Supporting Enhanced Perioperative Care In Emergency...mentioning
confidence: 99%